Personalized medicine: overview and comparison of challenges and opportunities for its implementation in the Brazilian public healthcare system (SUS) - Amanda da Cruz Nunes de Moraes; Silvya Stuchi-Maria-Engler (Brazilian Journal of Oncology, 2023)
The objective of this work is, through a literature review, to promote the debate on personalized medicine and acquire a broad view of the subject and its tools from the perspective of oncology, disseminate the topic, support, and encourage initiatives to implement its technologies in the Brazilian public healthcare system, collaborating for a sustainable ecosystem in the incorporation of technologies, and above all, with the health and quality of life of patients. The implementation of personalized medicine technologies in SUS is feasible and effective. The scenario is optimistic considering the latest updates from the Ministry of Health with the establishment of the Brazilian Genomes Program. With wise management of resources and actions focused on creating an infrastructure that supports it, the entire public healthcare system will be benefited and can take advantage of the improvements. Personalized medicine is the future of healthcare.